Anticancer Activity of Green Tea Polyphenols in Prostate Gland. (15th May 2012) - Davalli, Pierpaola; Rizzi, Federica; Caporali, Andrea; Pellacani, Davide; Davoli, Serena; Bettuzzi, Saverio; Brausi, Maurizio; D'Arca, Domenico
Abstract : Numerous evidences from prevention studies in humans, support the existence of an association between green tea polyphenols consumption and a reduced cancer risk. Prostate cancer is one of the most frequently diagnosed male neoplasia in the Western countries, which is in agreement with this gland being particularly vulnerable to oxidative stress processes, often associated with tumorigenesis. Tea polyphenols have been extensively studied in cell culture and animal models where they inhibited tumor onset and progression. Prostate cancer appears a suitable target for primary prevention care, since it grows slowly, before symptoms arise, thus offering a relatively long time period for therapeutic interventions. It is, in fact, usually diagnosed in men 50-year-old or older, when even a modest delay in progression of the disease could significantly improve the patients quality of life. Although epidemiological studies have not yet yielded conclusive results on the chemopreventive and anticancer effect of tea polyphenols, there is an increasing trend to employ these substances as conservative management for patients diagnosed with less advanced prostate cancer. Here, we intend to review the most recent observations relating tea polyphenols to human prostate cancer risk, in an attempt to outline better their potential employment for preventing prostate cancer.